(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2011)
Key words: Pelvic floor dysfunction; urogynaecology; stress urinary incontinence (SUI); pelvic organ prolapse (POP); overactive bladder (OAB); urodynamic studies (UDS) DOI: 10.3329/jcmcta.v21i2.7736 Journal of Chittagong Medical College Teachers’ Association 2010: 21(2):35-40